Uptake and distribution of natural radioactivity in rice from soil in north and west part of peninsular malaysia for the estimation of ingestion dose to man - Asaduzzaman, K.; Khandaker, Mayeen Uddin; Amin, Yusoff Mohd; Mahat, R.H. (Elsevier, 2015)
Paddy is the third most widely planted crop in Malaysia and most of the Malaysian people consume rice as their staple food. Hence, studies on the uptake of naturally occurring radionuclides by rice from soil of widely rice cultivated areas in Malaysia have been performed under normal field environments in order to evaluate various radiation hazards via rice consumption. The soil-to-rice grain transfer factors and the annual effective dose have been assessed for the natural radionuclides 226Ra, 232Th and 40K. The estimated transfer factors for 226Ra and 232Th were found far beyond compared to the IAEA reported value for rice. Among the detected radionuclides, 40K shows the highest transfer factor in all study locations but close to the IAEA reported range. The total effective dose obtained due to an ingestion of radionuclides via rice consumption was within the range of world average value (290 μSv y−1) compiled by the UNSCEAR (2000) in all study areas. On an average, the excess life time cancer risk (ELCR) values via rice consumption were found below the acceptable limit of 10−3 for radiological risk.